ChemInform Abstract: Phosphine/Palladium‐Catalyzed One‐Pot Synthesis of Functionalized 6H‐Benzo[c]chromenes. Issue 47 (November 2015) - Mo, Hanjie; Pan, Chengmin; Chen, Dingben; Chen, Di; Gao, Jianrong; Yang, Jianguo
Abstract: The synthesis of the title compounds proceeds in two steps: addition of the triple bond to the phenolic OH group followed by the ring closure reaction.